MarsSI: Martian surface data processing information system. (January 2018) - Quantin-Nataf, C.; Lozac'h, L.; Thollot, P.; Loizeau, D.; Bultel, B.; Fernando, J.; Allemand, P.; Dubuffet, F.; Poulet, F.; Ody, A.; Clenet, H.; Leyrat, C.; et al.
Abstract: MarsSI (Acronym for Mars System of Information, https://emars.univ-lyon1.fr/MarsSI/ ) is a web Geographic Information System application which helps managing and processing martian orbital data. The MarsSI facility is part of the web portal called PSUP (Planetary SUrface Portal) developed by the Observatories of Paris Sud (OSUPS) and Lyon (OSUL) to provide users with efficient and easy access to data products dedicated to the martian surface. The portal proposes 1) the management and processing of data thanks to MarsSI and 2) the visualization and merging of high level (imagery, spectral, and topographic) products and catalogs via a web-based user interface (MarsVisu). The portal PSUP as well as the facility MarsVisu is detailed in a companion paper (Poulet et al., 2018). The purpose of this paper is to describe the facility MarsSI. From this application, users are able to easily and rapidly select observations, process raw data via automatic pipelines, and get back final products which can be visualized under Geographic Information Systems. Moreover, MarsSI also contains an automatic stereo-restitution pipeline in order to produce Digital Terrain Models (DTM) on demand from HiRISE (High Resolution Imaging Science Experiment) or CTX (Context Camera) pair-images. This application is funded by the European Union's Seventh Framework Programme (FP7/2007–2013) (ERC project eMars, No. 280168) and has been developed in the scope of Mars, but the design is applicable to any other planetary body of the solar system. Highlights: MarsSI is a web application managing and processing Martian orbital data on demand. MarsSI proposes on demand automatic stereo-restitution from HiRISE or CTX pair-images. While developed in the scope of Mars, the design is applicable to any other planetary body of the solar system.